2001
DOI: 10.1038/90108
|View full text |Cite
|
Sign up to set email alerts
|

Genetic interactions between tumor suppressors Brca1 and p53 in apoptosis, cell cycle and tumorigenesis

Abstract: Breast cancer is a chief cause of cancer-related mortality that affects women worldwide. About 8% of cases are hereditary, and approximately half of these are associated with germline mutations of the breast tumor suppressor gene BRCA1 (refs. 1,2). We have previously reported a mouse model in which Brca1 exon 11 is eliminated in mammary epithelial cells through Cre-mediated excision. This mutation is often accompanied by alterations in transformation-related protein 53 (Trp53, encoding p53), which substantiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
350
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 344 publications
(372 citation statements)
references
References 29 publications
17
350
1
2
Order By: Relevance
“…The mutant glands appeared less dense than controls, and this abnormality was more impressive when the alveoli were visualized in high power images. Our previous studies indicated that mammary defects caused by Brca1 mutation could be rescued by p53 deficiency (Xu et al, 2001;Li et al, 2007). As Chk1 activity is regulated at least in part by Brca1 (Yarden and Brody, 2001), we were interested in investigating whether the developmental defect associated with Chk1 mutation could be rescued by simultaneous deletion of p53.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutant glands appeared less dense than controls, and this abnormality was more impressive when the alveoli were visualized in high power images. Our previous studies indicated that mammary defects caused by Brca1 mutation could be rescued by p53 deficiency (Xu et al, 2001;Li et al, 2007). As Chk1 activity is regulated at least in part by Brca1 (Yarden and Brody, 2001), we were interested in investigating whether the developmental defect associated with Chk1 mutation could be rescued by simultaneous deletion of p53.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, Chk1 deficiency yields profound abnormalities, as evidenced by mitotic catastrophe, which is much more severe than that caused by Brca1 mutation (Shen et al, 1998;Xu et al, 1999;Wang et al, 2004). This may account for the reason why absence of p53 could not rescue the lethality caused by Chk1 deficiency, although the absence of p53 is sufficient to suppress the lethality and growth defects associated with Brca1 mutation (Xu et al, 2001;Li et al, 2007). However, the abnormalities in multiple cell cycle checkpoints and cytokinesis in Chk1 mutant cells could eventually result in accumulation of genetic alterations that may cooperate with p53 deficiency to induce tumor formation.…”
Section: Discussionmentioning
confidence: 99%
“…In a subsequent study, Xu et al (2001b) examined the phenotype of the non-targeted homozygous deletion of Brca1 exon 11. Brca1 DEx11/DEx11 mice all died during late embryogenesis, due to widespread apoptosis.…”
Section: Brca1 Regulation Of the Proteomementioning
confidence: 99%
“…The relevance of apoptosis in cortical development (Haydar et al, 1999), the increased apoptosis of neuroepithelial cells observed in systemic Brca1 knockouts (Gowen et al, 1996;Xu et al, 2001), and the expression pattern of Brca1 in neural progenitors, when considered together, raise the intriguing possibility that Brca1 might have a role in the development of the cerebral cortex. Moreover, the apparent link between BRCA1 and the primary microcephaly genes ASPM (Bond et al, 2002;Zhong et al, 2005) and MCPH1 (Xu et al, 2004;Lin et al, 2005), whereby knockdown of either microcephaly gene leads to a decrease in BRCA1 levels, also leads to the question of whether BRCA1 has a role in brain size regulation.…”
Section: Introductionmentioning
confidence: 99%